2010
DOI: 10.1200/jco.2009.24.4491
|View full text |Cite
|
Sign up to set email alerts
|

Cytidine Deaminase Residual Activity in Serum Is a Predictive Marker of Early Severe Toxicities in Adults After Gemcitabine-Based Chemotherapies

Abstract: PURPOSE Anticipating toxicities with gemcitabine is an ongoing story, and deregulation in cytidine deaminase (CDA) could be associated with increased risk of developing early severe toxicities on drug exposure. PATIENTS AND METHODS A simple test to evaluate CDA phenotypic status was first validated in an animal model investigating relationships between CDA activity and gemcitabine-related toxicities. Next, relevance of this test as a marker for toxicities was retrospectively tested in a first subset of 64 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
104
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 22 publications
(16 reference statements)
6
104
4
1
Order By: Relevance
“…This study also demonstrates that CDA downregulation in BLM-expressing cells leads to a significant increase in SCE frequency and replication stress, potentially conferring a predisposition to cancer. A previous French study reported that 7% of adult patients with cancer treated with gemcitabine (5′-azacytidine, 2′,2′-difluorodeoxycytidine), a CDA substrate, had very low levels of CDA activity, rendering gemcitabine highly toxic 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrates that CDA downregulation in BLM-expressing cells leads to a significant increase in SCE frequency and replication stress, potentially conferring a predisposition to cancer. A previous French study reported that 7% of adult patients with cancer treated with gemcitabine (5′-azacytidine, 2′,2′-difluorodeoxycytidine), a CDA substrate, had very low levels of CDA activity, rendering gemcitabine highly toxic 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Severe GCB toxicity in NSCLC patients was reported in cases with heterozygous c.437CT variant and, to a lesser degree, in those with homozygous c.435TT variant (25,26). Interestingly, the latter was also found to be related to better response to GCB treatment, owing to reduced serum CDA concentration and higher exposure to active GCB metabolites (27,28). Heterozygous c.79A>C polymorphism was reported to cause severe leukopenia and neutropenia (14,(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Data on the relationship between CDA polymorphisms and GCB toxicity are inconsistent (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Severe GCB toxicity in NSCLC patients was reported in cases with heterozygous c.437CT variant and, to a lesser degree, in those with homozygous c.435TT variant (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations